Enlivening Spirits: Shaker Dance Ritual as Theopraxis - LaMothe, Kimerer (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2017)
In the history of dance and Christian theology, the United Society of Believers in the Second Coming of Christ, otherwise known as the Shakers, prove a unique case. Not only did the Shakers practice dancing for over 140 years as the central, constitutive ritual of a successful separatist religious socialism ; and not only did the Shakers mount a biblically informed theological defense of their dancing practice. The Shakers also elevated dancing alongside the Bible as a privileged medium of divine revelation. This paper mobilizes an ecokinetic approach in relation to the first two arcs of Shaker history to argue that the Shakers’ dancing serves as an authorizing source for their theological innovations. Dance is theopraxis.